Improving Mathematics Learning Outcomes using Problem Based Learning Models - Suhadi, Suhadi (Universitas Sebelas Maret, 2022)
Based on the observations of researchers, it was found that the learning in grade II is still centered on teachers because the learning model used is lectures. This study aims to find out the results of learning when teachers use PBL learning model. This research is a Class Action Research (CAR). The results showed that the learning steps of Problem Based Learning (PBL) that can be designed by teachers include problem orientation in learners, organizing learners to learn, guiding individual or group investigations, developing and presenting works, analyzing and evaluating problem solving processes. The implementation of PBL learning model can improve the math learning outcomes of grade II students at SD Negeri 2 Somosari in the 2020/2021 school year with the completion of classical learning of learners from 36.67% in the pre-cycle to 46.67% in cycle I and 76.67% in cycle II.